Given, A+B=90
Prove that
![\sqrt{ \frac{ \tan \alpha \tan \beta + \tan \alpha \cot \beta }{ \sin\alpha \sec \beta } - \frac{ { \sin( \beta ) }^{2} }{ \cos( { \beta }^{2} ) } } = \tan( \alpha ) \sqrt{ \frac{ \tan \alpha \tan \beta + \tan \alpha \cot \beta }{ \sin\alpha \sec \beta } - \frac{ { \sin( \beta ) }^{2} }{ \cos( { \beta }^{2} ) } } = \tan( \alpha )](https://tex.z-dn.net/?f=+%5Csqrt%7B+%5Cfrac%7B+%5Ctan+%5Calpha++%5Ctan+%5Cbeta++%2B++%5Ctan+%5Calpha++%5Ccot+%5Cbeta+%7D%7B+%5Csin%5Calpha++%5Csec+%5Cbeta++%7D++-++%5Cfrac%7B+%7B+%5Csin%28+%5Cbeta+%29+%7D%5E%7B2%7D+%7D%7B+%5Ccos%28+%7B+%5Cbeta+%7D%5E%7B2%7D+%29+%7D+%7D+%3D++%5Ctan%28+%5Calpha+%29+)
Attachments:
![](https://hi-static.z-dn.net/files/db9/f96b440ac942492bf9f7b0ed06f11467.jpg)
Answers
Answered by
0
Answer:
Step-by-step explanation:
Given, LHS = root tan a tan b + tan a cot b/sin a sec b - sin^2 b/cos^2 a
= root tan a tan(90-a) + tan a cot(90-a)/sin a sec(90-a) - sin^2(90-a)/cos^2 a
= root tan a.cot a + tan a.tana/sin a.cosec a - cos^2 a/cos^2 a
= root 1+tan^2 a/1 - 1
= root tan^2 a
= tan a.
Mark as brainliest please
rohitbagoriya1977:
hi
Similar questions